A new species of Amaranthus (Amaranthaceae) from Mexico - Sánchez-Del Pino, Ivonne; Pratt, Donald; Flores-Olvera, Hilda (Phytotaxa, 2017)
A new endemic species of Amaranthus—Amaranthus neei—from Mexico is described, illustrated, and compared to the putatively related species. A. neei is known from the Valley of Mexico (South of Hidalgo, Mexico city, and State of Mexico), Michoacán, Puebla, Veracruz, and Chiapas. The new species is a monoecious herb characterized by its long, pungent, erect or recurvate, bracts and bracteoles, (2–)3–5 minute pistillate sepals or absent, ovate, oblong to linear, apex acute to obtuse, and fruits circumscissile, irregularly dehiscent to indehiscent. Infrageneric circumscription of A. neei is discussed together with its critical taxonomic position within the currently accepted infrageneric classification of Amaranthus.